Photoresist composition based on carbon quantum dots and application thereof

By introducing surface-modified carbon quantum dots into the photoresist, combined with specific photosensitizers and non-diffusion agents, the problems of limited resolution and rough edges of the graphic line in high-precision and small-size pattern processing are solved, and high resolution and good patterning capabilities are achieved.

CN119535889APending Publication Date: 2025-02-28UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734562.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional organic photoresist has problems such as limited resolution, rough edges of the graphics, insufficient etch resistance and thermal stability in high-precision and small-size graphics processing.

Method used

Carbon quantum dots are used as photosensitizers to improve their dispersion and compatibility through surface modification, and combined with specific photosensitizers and non-diffusion agents, a high-performance photoresist composition is prepared.

Benefits of technology

It achieves high resolution (up to 100nm), good patterning ability and excellent photoelectric performance, and is compatible with a variety of lithography processes, making it easy to apply in existing semiconductor manufacturing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119535889A_ABST
    Figure CN119535889A_ABST
Patent Text Reader

Abstract

The invention provides a photoresist composition based on carbon quantum dots as well as a preparation method and application thereof. The photoresist composition comprises carbon quantum dots, a photosensitizer, an anti-diffusion agent and a photoresist solvent. The particle size of the carbon quantum dot is 2-10nm, and the surface is modified by functional groups. The photosensitizer is alpha-hydroxyethyl phenyl ketone and the like, the anti-diffusion agent is n-amyl alcohol and the like, and the photoresist solvent is an organic solvent such as methylbenzene and the like. The preparation method comprises the step of preparing the carbon quantum dots. The photoresist based on the carbon quantum dots prepared in the invention has higher resolution (up to sub-100nm), good patterning ability and excellent photoelectric properties, can form photoetching patterns through spin coating, exposure, development and other processes, is suitable for ultraviolet, extreme ultraviolet and electron beam photoetching, and can meet various micro-nano processing requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoresists, and in particular to a photoresist composition based on carbon quantum dots and applications thereof. Background Art

[0002] Photoresist is a key material in the photolithography process. It is mainly composed of a mixture of photosensitive resin, photosensitizer and solvent. It is a key material for micro-graphic processing in microelectronics technology and is widely used in the fields of integrated circuit and micro-nano device manufacturing. Photoresist plays a vital role in the photolithography process through its photochemical response to specific wavelengths. Its main functions include precise pattern transfer, forming and protecting the cover substrate, preventing etching or ion implantation, etc.

[0003] Traditional photoresists mostly use organic polymers or organic single-molecule resins. Due to the large molecular weight and wide distribution range of polymers, the resolution is limited. As chip manufacturing processes continue to shrink, the critical dimensions of photolithography patterns are getting smaller and smaller, which puts stringent requirements on photolithography technology, making it difficult for traditional organic photoresists to meet higher precision requirements. Although the sensitivity can be improved by adding sensitizers, the free radicals generated by the photochemical process will further diffuse freely and irregularly during the post-baking process, resulting in high roughness on the edges of the graphic lines, affecting the patterning accuracy. At the same time, the etching resistance, thermal stability and other properties of some traditional organic photoresists need to be improved.

[0004] Specific inorganic material-containing photoresists have a higher light absorption cross section, so they can improve sensitivity and reduce the roughness of pattern structures caused by photon emission noise. By modifying the surface of inorganic materials to form stable chemical bonds, it can not only improve the compatibility with solvents, but also make it compatible with existing semiconductor manufacturing processes. Therefore, organic / inorganic hybrid photoresists can significantly improve the photolithography performance of existing traditional photoresists, but existing materials have limitations such as limited element types and high costs.

[0005] Carbon quantum dots have good biocompatibility, low toxicity, and high stability. Their surfaces are rich in functional groups and are easy to chemically modify and functionalize. By modifying the surface of carbon quantum dots, they can be made photosensitized, thereby achieving photolithographic patterning. Therefore, introducing carbon quantum dots into the photoresist system is expected to improve the performance of photoresists and expand their application range. Summary of the invention

[0006] The present invention provides a method for preparing a photoresist composition based on carbon quantum dots, which comprises inorganic quantum dots, a photosensitizer, an anti-diffusion agent and a photoresist solvent, wherein the inorganic quantum dots are carbon quantum dots. The method is characterized in that it comprises the following steps:

[0007] Preparation of carbon quantum dots:

[0008] S1. Dissolve 2g citric acid and 1g ethylenediamine in 20mL deionized water and stir well.

[0009] S2. Transfer the mixed solution to a reactor and perform hydrothermal reaction at 200°C for 6 hours.

[0010] S3. After the reaction is completed, the mixture is naturally cooled to room temperature, and the product is dialyzed for 24 hours using a dialysis bag with a molecular weight cutoff of 1000 Da to obtain carbon quantum dots with surface modified with amino groups.

[0011] Photoresist preparation:

[0012] S4. Take a certain amount of carbon quantum dots and disperse them in a certain amount of solvent, and disperse them by ultrasonic for 20 minutes.

[0013] S5. Add a certain amount of photosensitizer and a certain amount of anti-diffusion agent, and continue ultrasonic dispersion for 20 minutes to obtain a photoresist composition.

[0014] Lithography:

[0015] S6. Spin-coat the photoresist on the glass sheet at a speed of 2000 rpm for 90 seconds and pre-bake at 90°C for 3 minutes. Use electron beam exposure (30-100 mJ / cm 2 ), after exposure, post-bake at 110°C for 2 minutes, and develop with a developer for 90 seconds to obtain a photoresist pattern with a resolution of 80nm.

[0016] According to the present invention, in the photoresist composition, the particle size of the carbon quantum dots is preferably 2-10 nm.

[0017] According to the present invention, the surface of the carbon quantum dots is modified by organic functional groups such as amino or carboxyl to improve its dispersibility and compatibility in the photoresist system, and the mass of the carbon quantum dots accounts for 1%-5% of the total mass of the photoresist composition.

[0018] According to the present invention, in the photoresist composition, the photosensitizer is selected from α-hydroxyethyl phenyl ketone, 2-isopropylthioxanthone, etc., and its mass accounts for 0.1%-1.0% of the total mass of the photoresist composition.

[0019] According to the present invention, in the photoresist composition, the diffusion prevention agent is a C5-12 saturated fatty alcohol such as n-pentanol and 2,3-dimethyl-2-butanol, accounting for 0.01%-0.10% of the total mass.

[0020] According to the present invention, in the photoresist composition, the photoresist solvent is an organic solvent selected from a mixture of one or more of toluene, xylene, propylene glycol monomethyl ether acetate, and cyclopentanone, which accounts for the balance of the photoresist composition.

[0021] The invention also provides a photoresist pattern, which is obtained by forming a coating layer with a photoresist composition and then exposing the coating layer.

[0022] The present invention also provides a method for preparing a photoresist pattern, comprising applying the photoresist composition on a substrate to obtain a photoresist coating, and obtaining different patterns after the photoresist coating is exposed.

[0023] According to the present invention, the application method is spin coating.

[0024] According to the present invention, the photoresist coating is a thin film.

[0025] According to the present invention, the exposure method includes ultraviolet exposure, extreme ultraviolet exposure, electron beam exposure, etc.

[0026] Furthermore, the present invention also provides an application of the photoresist composition, which is used for processing micro-nano devices.

[0027] After the photoresist is patterned and then heat-treated, it has good electrical conductivity and can be directly used in the processing of micro-nano devices.

[0028] Beneficial Effects

[0029] (1) High-performance photoresist: Combined with the unique properties of carbon quantum dots, the photoresist has high resolution (up to sub-100nm), good patterning ability and excellent optoelectronic properties.

[0030] (2) Good process compatibility: It is compatible with a variety of lithography processes, such as ultraviolet lithography, extreme ultraviolet lithography and electron beam lithography, which facilitates integration and application in existing semiconductor manufacturing processes.

[0031] (3) Multifunctional application potential: It has shown broad application prospects in many fields such as optoelectronic devices, biomedicine and micro-nano optics, and provides new material options for the manufacture of high-performance micro-nano devices and systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a flow chart for preparing the carbon quantum dot photoresist composition. DETAILED DESCRIPTION

[0033] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0034] Embodiment 1:

[0035] Preparation of carbon quantum dots: 2g of citric acid and 1g of ethylenediamine were dissolved in 20mL of deionized water, stirred evenly and transferred to a reactor for hydrothermal reaction at 200°C for 6h. After the reaction was completed, it was naturally cooled to room temperature, and the product was dialyzed for 24h with a dialysis bag with a molecular weight cutoff of 1000Da to obtain carbon quantum dots with surface modified with amino groups. According to the dynamic light scattering test (DLS), the particle size was less than 11nm, the average particle size was about 8nm, and the particle size distribution of the quantum dots was uniform.

[0036] Photoresist preparation and photolithography: 0.3g carbon quantum dots were dispersed in 9.65g toluene, ultrasonically dispersed for 20min, 0.06g 2-isopropylthioxanthone and 0.006g n-pentanol were added, and ultrasonic dispersion was continued for 20min to obtain a photoresist composition. The photoresist was spin-coated on a glass sheet at a spin speed of 2000rpm for 90s and pre-baked at 90℃ for 3min. Electron beam exposure was used with an exposure dose of 50mJ / cm 2 After exposure, it was post-baked at 110°C for 2 minutes and developed with a developer for 90 seconds to obtain a photoresist pattern with a resolution of 80nm.

[0037] Embodiment 2:

[0038] Preparation of carbon quantum dots: The preparation method is the same as that in Example 1.

[0039] Photoresist preparation and photolithography: 0.5g carbon quantum dots were dispersed in 9.35g toluene, ultrasonically dispersed for 20min, 0.1g 2-isopropylthioxanthone and 0.01g n-pentanol were added, and ultrasonic dispersion was continued for 20min to obtain a photoresist composition. The photoresist was spin-coated on a glass sheet at a spin speed of 2000rpm for 90s and pre-baked at 90℃ for 3min. Electron beam exposure was used with an exposure dose of 30mJ / cm 2 After exposure, it was post-baked at 110°C for 2 minutes and developed with a developer for 90 seconds to obtain a photoresist pattern with a resolution of 140nm.

[0040] Embodiment 3:

[0041] Preparation of carbon quantum dots: The preparation method is the same as that in Example 1.

[0042] Photoresist preparation and photolithography: 0.3g carbon quantum dots were dispersed in 9.65g toluene, ultrasonically dispersed for 20min, 0.01g α-hydroxyethyl phenyl ketone and 0.008g n-pentanol were added, and ultrasonic dispersion was continued for 20min to obtain a photoresist composition. The photoresist was spin-coated on a glass sheet at a spin speed of 2000rpm for 90s and pre-baked at 90℃ for 3min. Electron beam exposure was used with an exposure dose of 100mJ / cm 2After exposure, it was post-baked at 110°C for 2 minutes and developed with a developer for 90 seconds to obtain a photoresist pattern with a resolution of 110nm.

[0043] Embodiment 4:

[0044] Preparation of carbon quantum dots: The preparation method is the same as that in Example 1.

[0045] Photoresist preparation and photolithography: 0.3g carbon quantum dots were dispersed in 9.65g toluene, ultrasonically dispersed for 20min, 0.06g α-hydroxyethyl phenyl ketone and 0.006g n-pentanol were added, and ultrasonic dispersion was continued for 20min to obtain a photoresist composition. The photoresist was spin-coated on a glass sheet at a spin speed of 2000rpm for 90s and pre-baked at 90℃ for 3min. Electron beam exposure was used with an exposure dose of 80mJ / cm 2 After exposure, it was post-baked at 110°C for 2 minutes and developed with a developer for 90 seconds to obtain a photoresist pattern with a resolution of 90nm.

[0046] Embodiment 5:

[0047] Preparation of carbon quantum dots: The preparation method is the same as that in Example 1.

[0048] Photoresist preparation and photolithography: 0.1g carbon quantum dots were dispersed in 9.85g toluene, ultrasonically dispersed for 20min, 0.01g 2-isopropylthioxanthone and 0.001g n-pentanol were added, and ultrasonic dispersion was continued for 20min to obtain a photoresist composition. The photoresist was spin-coated on a glass sheet at a spin speed of 2000rpm for 90s and pre-baked at 90℃ for 3min. Electron beam exposure was used with an exposure dose of 50mJ / cm 2 After exposure, it was post-baked at 110°C for 2 minutes and developed with a developer for 90 seconds to obtain a photoresist pattern with a resolution of 120nm.

[0049] Comparative Example 1

[0050] The method of Comparative Example 1 is similar to that of Example 1, except that the solvent is replaced with xylene.

[0051] Comparative Example 2

[0052] The method of Comparative Example 2 is similar to that of Example 1, except that no anti-diffusion agent is added.

[0053] Comparative Example 3

[0054] The method of Comparative Example 3 is similar to that of Example 1, except that the anti-diffusion agent is replaced with 2,3-dimethyl-2-butanol.

[0055] By changing the component content and photosensitizer type of the photoresist composition, it was found that too high a carbon quantum dot content would affect the photoresist resolution. It may be that the high concentration of carbon quantum dots affects the dispersion uniformity of the dispersant and the film-forming properties of the spin coating. By changing the type of photosensitizer in the photoresist composition, it was found that the photoresist with α-hydroxyethyl phenyl ketone as the photosensitizer has a smoother pattern edge under ultraviolet exposure, but the exposure time is longer; the photoresist with 2-isopropylthioxanthone as the photosensitizer has a fast exposure speed, but the pattern edge roughness is slightly higher. By changing different exposure doses, it was found that for the photoresist with 2-isopropylthioxanthone as the photosensitizer, at an exposure dose of 50mJ / cm 2 When the exposure dose is 80mJ / cm 2 The lithography performance of the corresponding example is listed in Table 1.

[0056] Table 1 Comparison of lithography performance of different photoresists

[0057] Examples <![CDATA[Sensitivity (mJ / cm 2 )]]> Resolution(nm) Example 1 50 80 Example 2 30 140 Example 3 100 110 Example 4 80 90 Example 5 50 120 Comparative Example 1 50 80 Comparative Example 2 50 120 Comparative Example 3 50 95

[0058] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A photoresist composition comprising carbon quantum dots, a photosensitizer, an anti-diffusion agent and a photoresist solvent. Preparation of carbon quantum dots: S1. Dissolve 2g citric acid and 1g ethylenediamine in 20mL deionized water and stir well. S2. Transfer the mixed solution to a reactor and perform hydrothermal reaction at 200°C for 6 hours. S3. After the reaction is completed, the mixture is naturally cooled to room temperature, and the product is dialyzed for 24 hours using a dialysis bag with a molecular weight cutoff of 1000 Da to obtain carbon quantum dots with surface modified with amino groups. Photoresist preparation: S4. Take a certain amount of carbon quantum dots and disperse them in a certain amount of solvent, and disperse them by ultrasonic for 20 minutes. S5. Add a certain amount of photosensitizer and a certain amount of anti-diffusion agent, and continue ultrasonic dispersion for 20 minutes to obtain a photoresist composition. Photolithography: S6. Spin-coat the photoresist on the glass sheet at a speed of 2000 rpm for 90 seconds and pre-bake at 90°C for 3 minutes. Use electron beam exposure (30-100 mJ / cm 2 ), after exposure, post-bake at 110°C for 2 minutes, and develop with a developer for 90 seconds to obtain a photoresist pattern with a resolution of 80nm.

2. The method for preparing carbon quantum dots according to claim 1, characterized in that: In step S2, the reaction temperature is 200° C. and the reaction time is 6 h.

3. The photoresist composition according to claim 1, characterized in that The photoresist components in steps S4 and S5 include the following components by weight: 1%-5% carbon quantum dots, 0.1%-1.0% photosensitizer, 0.01%-0.10% anti-diffusion agent, and the balance of photoresist solvent.

4. The photoresist composition according to claim 1, characterized in that The solvent in step S4 is an organic solvent selected from a mixture of one or more of toluene, xylene, propylene glycol monomethyl ether acetate, and cyclopentanone.

5. The photoresist composition according to claim 1, characterized in that In step S5, the photosensitizer is selected from at least one of α-hydroxyethyl phenyl ketone and 2-isopropylthioxanthone.

6. The photoresist composition according to claim 1, characterized in that In step S5, the diffusion prevention agent is selected from at least one of n-pentanol, 2,3-dimethyl-2-butanol and other C5-12 saturated fatty alcohols.

7. The photoresist composition according to any one of claims 1 to 6, characterized in that: The surface of the carbon quantum dots has an organic stabilizer, and the organic stabilizer, for example, the surface of the carbon quantum dots is modified by functional groups such as amino groups or carboxyl groups.

8. The photoresist composition according to any one of claims 1 to 7, characterized in that Used to improve photoresist resolution, patterning capabilities and optoelectronic performance.